Community-based counselling programme for pregnant women with alcohol problems in Cape Town, South Africa: a qualitative study of the views of pregnant women and healthcare professionals - Petersen Williams, Petal; Erasmus, Jodilee; Myers, Bronwyn; Nadkarni, Abhijit; Fuhr, Daniela C. (Frontiers in Psychiatry, 2023)
Introduction: South Africa lacks services to detect and address alcohol use during pregnancy, particularly outside of health-care facilities. This study aimed to explore pregnant women and healthcare providers' perceptions of the acceptability, feasibility and appeal of a communitybased counselling programme for pregnant women with alcohol problems.Methods: Twenty-eight in-depth interviews with pregnant women who drink, Community Health Workers (CHWs) and antenatal service providers were conducted. Transcribed interviews were analyzed thematically using a combined deductive and inductive approach.Results: Women reported feeling uncomfortable seeking help for their alcohol use at antenatal clinics, limiting usefulness of current support services. All stakeholders perceived a communitybased intervention to be acceptable and feasible as it could be integrated with other CHW-delivered services. Participants thought an intervention should facilitate early linkage to antenatal services and should include partners or family members. The feasibility of an intervention may depend on the relationship between CHWs and clinic-based antenatal staff, and their relationships with pregnant women. Intensive training, supervision and support is therefore required to ensure the programme is delivered as planned. Clinic and community challenges to implementation were raised. Clinic-level challenges included shortage of space, staff capacity, high number of pregnant women, long waiting times, financial burden of having to travel to a clinic, lack of comfort and privacy and staff attitudes. Community-level challenges included crime, lack of privacy, lack of attention given competing interests in the home, fear due to abuse, and stigma and discrimination from other community members. Suggestions for overcoming these challenges were provided.Findings provide essential information to facilitate the adaptation of a communitybased alcohol counselling programme for greater acceptability, feasibility and cultural appropriateness for the South African context. Intensive training, supervision and support is required to ensure the programme is delivered as planned.